Patterns of second primary malignancies in carcinoma larynx and hypopharynx following surgical management - Ganga, Veena B.; Ramachandrappa, Krishnappa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The objective was to determine the incidence of second primary in patients with squamous cell carcinoma larynx and hypopharynx following surgical management with or without adjuvant treatment. Methods: A retrospective quantitative descriptive study was conducted on 289 patients who underwent surgical management of squamous cell carcinoma (SCC) of larynx and hypopharynx with or without adjuvant treatment and later developed second primary. This study comprised of patients undergoing treatment during the time period of January 2016 to January 2019 at the department of head and neck surgery, Kidwai institute of oncology. Results: Second primary malignancies (SPM) developed in 3.1% of patients within a median follow up period of 28 months. Majority of the second primaries developed in patients with hypopharyngeal malignancy. Conclusions: SPMs are amongst the leading causes of mortality in patients with SCC larynx and hypopharynx. Hence careful surveillance is essential for the early detection of a second primary.